Procedure-Related Complication of Willis Covered Stent in the Treatment of Blood Blister-Like Aneurysm: Stent Detachment from Dilating Balloon - Zhang, Yuxiang; Zhang, Yupeng; Liang, Fei; Jiang, Chuhan (Frontiers in Neurology, 2017)
The use of Willis covered stent (WCS) for intracranial aneurysms has increased based on the promising results of previous studies about its safety and effectiveness. With the accumulation of cases, reports about peri-procedural complications are emerging. In our department, 25 patients were treated with WCS during December 2015 to March 2017. We here reported an unexpected technical complication occurred in the treatment with the WCS for a blood blister-like aneurysm (BBA). During the procedure, the distal end of the stents detached from the dilating balloon partially or as a whole. This was attributed to the tortuosity of the access route and the extracorporeal gas exhaust maneuver. Then we applied a half-dilating technique to retrieve the detached stent. The procedures were detailed in this report and the possible reasons and approaches to avoid it were explored.